DECIDING OPTIMAL SPECIFICATION LIMITS AND PROCESS ADJUSTMENTS UNDER QUALITY LOSS FUNCTION AND PROCESS CAPABILITY INDICES - Kao, Shih-Chou (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
In traditional screw manufacturing, if buyers want to have high quality products, they have to pay the appreciate quality costs to their manufacturers. To satisfy the quality requirements of buyers with minimum loss of quality costs, this study proposes a modified totally expected quality loss model using Taguchi’s quality loss function and process capability indices for normal and non-normal distributions. The three-parameter Weibull distribution is used to estimate a skewed process. These models determine the optimal adjusted process mean, adjusted process standard deviation and specification limits based on the minimum costs and process capability requirements of buyers. This study also considers the design of optimal adjusted process parameters and specification limits using two examples: the hexagon head cap screw, and oil seal.